2016
DOI: 10.1080/1828051x.2016.1175325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary surfactin supplementation on growth performance, intestinal digestive enzymes activities and some serum biochemical parameters of tilapia (Oreochromis niloticus) fingerlings

Abstract: This trial was conducted to investigate the effects of supplementary surfactin on growth performance, intestinal digestive enzymes activities and some serum biochemical parameters of tilapia (Oreochromis niloticus) fingerlings. Three hundred and twenty fish were randomly divided into four treatment groups with four replicates in each group and 20 fish in each replicate. The dietary surfactin levels of four treatment groups were 0 (control group), 50, 100 and 200 mg/kg. The trial period was 7 weeks. Compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Quesada et al [21] reported that grapeseed procyanidin extract (GSPE) treatment slightly lowered the content of TG and CHO in rat livers. Moreover, Zhai et al [23] reported that quercetin decreased the serum TG content in tilapia (freshwater fish), which may be helpful for avoiding pathological changes of fatty liver. Kuipers et al [24] also reported that quercetin decreased the plasma TG level of 9week-old mice.…”
Section: Effects Of Quercetin On the Lipid Metabolism In Hepatocytes From Aa Broilersmentioning
confidence: 99%
“…Quesada et al [21] reported that grapeseed procyanidin extract (GSPE) treatment slightly lowered the content of TG and CHO in rat livers. Moreover, Zhai et al [23] reported that quercetin decreased the serum TG content in tilapia (freshwater fish), which may be helpful for avoiding pathological changes of fatty liver. Kuipers et al [24] also reported that quercetin decreased the plasma TG level of 9week-old mice.…”
Section: Effects Of Quercetin On the Lipid Metabolism In Hepatocytes From Aa Broilersmentioning
confidence: 99%
“…Bi (2018) revealed that the antimicrobial peptides produced by Bacillus subtilis mutHS-301 had stable bacteriostatic activity against V. parahaemolyticus. Zhai et al, 2016 In addition, in the present study, excessive supplementation of dietary antimicrobial peptide APSH-07 (22.5 mg/kg) had significantly negative effects on the growth, immune and antioxidation responses and the disease resistance of abalone to V. parahaemolyticus. Similar results were found in previous studies in yellow catfish Pelteobagrus fulvidraco (Chen et al, 2007), common carp (Dong et al, 2019) and tilapia (Zhai et al, 2016).…”
Section: Discussionmentioning
confidence: 49%
“…Apart from interacting directly with pathogens and breaking down cell membranes by interacting with certain bacterial components (Chou, Wen, Kuo, Lin, & Chen, 2010), antimicrobial peptides also play a role by modulating the adaptive immune response (Chou et al., 2010; Liu et al., 2018; Lu, 2018; Oppenheim, Biragyn, Kwak, & Yang, 2003) or acting as chemokines to recruit other effector cells (Chertov et al., 1996). In addition, some beneficial effects of antimicrobial peptides on growth performance and non‐specific immunity have been reported in aquaculture animals, such as shrimp Litopenaeus vannamei and tilapia ( Oreochromis niloticus × O. aureus , and O. niloticus ) (Shi et al., 2014; Xin et al, 2015; Zhai, Shi, & Chen, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the metabolite surfactin produced by B. subtilis was shown to be effective in improving growth performance, alleviating expression of intestinal inflammatory genes and having a regulatory effect on the intestinal microbiota in broilers [48] . In addition, the addition of antibacterial peptide surfactin to tilapia ( Oreochromis niloticus ) feed can improve intestinal health by increasing the height of intestinal folds, regulating intestinal flora and increasing intestinal antioxidant capacity [49] . A class of widely used lipopeptides (fengycins) produced by Bacillus has been shown to eliminate Staphylococcus aureus colonizing the human gut by inhibiting population sensing, a process by which bacteria respond to their population density by altering their genetic regulation [50] .…”
Section: Potential Applications and Beneficial Roles Of Surfactinmentioning
confidence: 99%